2015
DOI: 10.1128/jvi.01178-15
|View full text |Cite
|
Sign up to set email alerts
|

P2X1 Receptor Antagonists Inhibit HIV-1 Fusion by Blocking Virus-Coreceptor Interactions

Abstract: HIV-1 Env glycoprotein-mediated fusion is initiated upon sequential binding of Env to CD4 and the coreceptor CXCR4 or CCR5. Whereas these interactions are thought to be necessary and sufficient to promote HIV-1 fusion, other host factors can modulate this process. Previous studies reported potent inhibition of HIV-1 fusion by selective P2X1 receptor antagonists, including NF279, and suggested that these receptors play a role in HIV-1 entry. Here we investigated the mechanism of antiviral activity of NF279 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 63 publications
(102 reference statements)
0
32
0
Order By: Relevance
“…First, the antagonists used in these studies are specific for P2X7 receptors compared with other P2X receptors or other receptors and channels but may show off‐target activity. Such a case was reported recently for a P2X1 antagonist that also inhibits the activity of CCR5 and CXCR4 (Giroud et al, ). Second, the tissue and cellular distribution of P2X7 is still unclear; antibodies and mouse reporter gene lack specificity or can reasonably be questioned.…”
Section: Purinergic Signaling In Epilepsymentioning
confidence: 96%
“…First, the antagonists used in these studies are specific for P2X7 receptors compared with other P2X receptors or other receptors and channels but may show off‐target activity. Such a case was reported recently for a P2X1 antagonist that also inhibits the activity of CCR5 and CXCR4 (Giroud et al, ). Second, the tissue and cellular distribution of P2X7 is still unclear; antibodies and mouse reporter gene lack specificity or can reasonably be questioned.…”
Section: Purinergic Signaling In Epilepsymentioning
confidence: 96%
“…There is a growing body of evidence that implicates purinergic receptors and both selective and non-selective antagonists of these receptors in HIV-1 infection [99][100][101][102][103][104][105]. Our laboratory and others have explored the role of purinergic receptors in HIV-1 infection and have reported that purinergic receptor antagonists can block HIV-1 infection and reduce inflammatory cytokine production associated with infection [96,106,107]. More specific probing appears to implicate drugs that target purinergic receptors in the inhibition of HIV-1 viral membrane fusion.…”
Section: Purinergic Receptors and Hiv-1mentioning
confidence: 99%
“…Hazleton, et al, demonstrated that purinergic receptors play a key role in HIV-1 replication in macrophages through selective pharmacologic inhibition of P2RX1, P2RX7, and P2RY1 [93]. Giroud, et al described a role for P2RX1 in blocking HIV-1 binding to the chemokine receptors CCR5 and CXCR4 [106]. Swartz, et al, demonstrated that non-selective antagonists of P2X receptors can inhibit HIV-1 infection of CD4 + lymphocytes through both cell-to-cell and cell-free mechanisms [96].…”
Section: Purinergic Receptors and Hiv-1mentioning
confidence: 99%
See 2 more Smart Citations